Synovial macrophages: from ordinary eaters to extraordinary multitaskers. Issue 5 (May 2021) - Hannemann, Nicole; Apparailly, Florence; Courties, Gabriel
Abstract : Like other tissues, joints contain resident macrophages, and their diversity is only beginning to be characterized. Based on the highlights of recent studies, we discuss where current challenges lie and propose new avenues for future research in the osteoarticular field.